2022
DOI: 10.3390/pathogens11060695
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Fungal Formulation with the Nematophagous Fungus Pochonia chlamydosporia in the Biological Control of Bovine Nematodiosis

Abstract: In the control of bovine worms, biological control by nematophagous fungi stands out, especially Pochoniachlamydosporia which causes the destruction of helminth eggs. This study aims to test the effectiveness of a formulation containing the nematophagous fungus Pochonia chlamydosporia isolated for the biological control of bovine nematodiosis. Twelve cattle were divided into two groups: control group (GC) and the group that received the formulation (GT). Feces and pasture samples were collected for the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…could collaborate with the reduction of nematode eggs and probably reduce the number of recovered lavas; since acting alone or in association with D. flagrans and M. thaumasium , it reduced the number of cyathostomine larvae by 73.2%, 86.8%, and 77.3%, respectively [ 30 ]. However, when it was used as the only agent in field evaluations, it was unable to control the free-life stages of bovine gastrointestinal nematodes [ 20 ]. Therefore, considering the reduction of eggs, it is unlikely that D. flagrans contributed significantly to the results presented.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…could collaborate with the reduction of nematode eggs and probably reduce the number of recovered lavas; since acting alone or in association with D. flagrans and M. thaumasium , it reduced the number of cyathostomine larvae by 73.2%, 86.8%, and 77.3%, respectively [ 30 ]. However, when it was used as the only agent in field evaluations, it was unable to control the free-life stages of bovine gastrointestinal nematodes [ 20 ]. Therefore, considering the reduction of eggs, it is unlikely that D. flagrans contributed significantly to the results presented.…”
Section: Resultsmentioning
confidence: 99%
“…Duddingtonia flagrans has been widely studied, and there are already commercial products which allow the implementation of biological control for parasites in animal production [ 12 , 17 , 18 , 19 ]. The association between different species of fungi is important to expand the spectrum of action of fungal formulations, especially if the fungi act on different targets of the life cycle of the parasites [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viña et al created a new formulation with D. flagrans and deconstrued an efficient solution to decrease the risk of infection among dogs maintained in shelters, which is recommended [ 2 ]. Fonseca et al, with a formulation with fungus Pochonia chlamydosporia , concluded that the rapid transition from egg to larvae stage was not affected by fungus Pochonia chlamydosporia ; therefore, the fungal formulation containing Pochonia chlamydosporia was not efficient in the biological control of bovine gastrointestinal nematodes [ 3 ]. The results of Luca et al indicated an ovicidal action of Pythium oligandrum , supporting the prospects of its use in the decontamination methods of various surfaces or environments where ascarid eggs from carnivores are found [ 4 ].…”
mentioning
confidence: 99%